2015
DOI: 10.3389/fmicb.2015.00051
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins IbpA and IbpB are required for NlpI-participated cell division in Escherichia coli

Abstract: Lipoprotein NlpI of Escherichia coli is involved in the cell division, virulence, and bacterial interaction with eukaryotic host cells. To elucidate the functional mechanism of NlpI, we examined how NlpI affects cell division and found that induction of NlpI inhibits nucleoid division and halts cell growth. Consistent with these results, the cell division protein FtsZ failed to localize at the septum but diffused in the cytosol. Elevation of NlpI expression enhanced the transcription and the outer membrane loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…This approach was chosen to minimize the changes in the secondary structure of the mRNA, as ibpA and ibpB genes are arranged in a single operon and transcribed into polycistronic mRNA. However, as reported previously [39], nonsense mutations in either ibpA or ibpB resulted in the increase in the cellular level of the remaining sHsp expressed at heat shock conditions as compared to the wild type strain (Fig 9A).…”
Section: Resultssupporting
confidence: 84%
“…This approach was chosen to minimize the changes in the secondary structure of the mRNA, as ibpA and ibpB genes are arranged in a single operon and transcribed into polycistronic mRNA. However, as reported previously [39], nonsense mutations in either ibpA or ibpB resulted in the increase in the cellular level of the remaining sHsp expressed at heat shock conditions as compared to the wild type strain (Fig 9A).…”
Section: Resultssupporting
confidence: 84%
“…The protein-protein interaction between PhoP and Pat or CobB were detected by Bacterial Two-Hybrid System (Stratagene) according to the previous procedure [ 57 ]. The phoP and pat or cobB genes were cloned into pBT and pTRG, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the high levels of inflammation characterizing IBD likely affect the microbiota as they do the host, inducing molecular and physiological changes. It was found that in response to harsh environments E. coli —which is found enriched in IBD patients (Table 1 )—could up-regulate the ibpA and ibpB genes belonging to the stress response regulon, which are involved in cell division, signal transduction and intestinal adhesion (Zuckert, 2014 ; Tao et al, 2015 ). In the IL10 −/− IBD model mouse inoculated with a murine isolate of colitis-inducing E. coli (NC101), ibpA and ibpB were found to be activated, presumably to cope with the high amounts of reactive oxygen species induced by intestinal inflammation and—possibly—by the increased temperature caused by inflammation (Patwa et al, 2011 ).…”
Section: Pathologies With Altered Gi Microbiomementioning
confidence: 99%